Optimalisasi Pelatihan Penyutradaraan untuk Meningkatkan Keterampilan dan Memperluas Peluang Masuk Dunia Kerja pada Anggota Teach4Hope di KitaBisa.com - Owie, Anggra Agastyassa; Wati, Wahyu Utami (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This community service activity aims to improve skills and provide opportunities for orphans, poor people, and people with disabilities in the world of film through director training. The method involves the active participation of participants in the preparation, implementation, and evaluation stages. The training was held on July 7-8, 2023, at the Yogyakarta Film Academy with a focus on understanding directors, including screenplay scripts, locations, characterization, timing, and director responsibilities. A total of 15 participants produced a film entitled "Ulat Becomes a Butterfly," which was uploaded on the Teach4Hope Indonesia YouTube page. This activity provides free education and job training, utilizes technology to create enlightening and inspiring film works, and has a positive impact on participants by increasing their skills and independence in the world of film.